Evaluating basic chest pass skills in the 21st century using chest pass automatic board 2.0 - Dzihan Khilmi Ayu Firdausi; Muhammad Eka Mardyansyah Simbolon; Ahmad Muchlisin Natas Pasaribu; Indra Dwisaputra; Diah Retno Arum sari; Catur Pebriandini (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Introduction: This research develops an automated tool to measure the chest pass ability in basketball. We developed this measurement to reduce human error in assessing the chest pass ability in basketball.